Development of speed controller for inverter FED induction motor - Muhd Hasif, Juhari (2010)
Normally variable speed control was performed by some type of d.c. motor. Today, the development of power semiconductors has resulted in the utilization of inverter circuits for variable speed control of induction motor. This project is to develop the application of inverter which can control the speed of induction motor by using PI controller. Inverters are circuit that convert DC to AC. The function of inverter is to create an AC voltage by using a DC voltage source, the voltage source that used DC voltage commonly batteries. Pulse Width Modulation (PWM) technique is considered as one solution for harmonic reduction and increasing the motor efficiency. Previous study regarding the performance on the traditional Pulse Width Modulation (PWM) inverter is carried out and it was found that the performance is not ideal. Therefore an improvement on the traditional PWM inverter is carried out by inserting a Proportional Integral (PI) controller to regulate and stabilize the output voltage of the inverter. This work was applied close-loop variable speed drive for single-phase induction motor using voltage control. The proposed drive system is simulated using Matlab/ Simulink, its results were compared with the hardware experimental results. The simulation and laboratory results proved that the drive system could be used for the speed control of a single phase induction motor with wide speed range